Ultrastructural Morphology and Nuclear Maturation Rates of Immature Equine Oocytes Vitrified with Different Solutions and Exposure Times - Curcio, Bruna R.; Gastal, Melba O.; Pereira, Gabriel R.; Corcini, Carine D.; Landim-Alvarenga, Fernanda C. [UNESP]; Barros, Severo S.; Nogueira, Carlos E. W.; Deschamps, Joao Carlos; Gastal, Eduardo L. (Elsevier B.V., 2014)
Ultrastructural morphological injuries and maturation rates were investigated in equine oocytes exposed to vitrification solutions (VS) containing synthetic ice blockers (SIBs) during different exposure times. In experiment 1, compact cumulus-oocyte complexes (COCs; n = 30) were randomly allocated to treatments: (1) fresh fixed (control); (2) VS-1 (1.4 M dimethyl sulfoxide [DMSO] + 1.8 M ethylene glycol LEG] + 1% SIB) for 3 minutes of equilibrium time and VS-2 (2.8 M DMSO + 3.6 M EG + 0.6 M sucrose + 1% SIB) for 1 minute (Eq-long); and (3) VS-1 for 1.5 minutes and VS-2 for 30 seconds (Eq-short). In experiment 2, compact (n = 248) and expanded (n = 264) COCs were evenly distributed to the following treatments: (1) immediate maturation in vitro (control); (2) vitrification using the Eq-short protocol as in experiment 1; and (3) vitrification using a stock solution containing 2.8 M formamide, 2.8 M DMSO, 2.7 M EG, 7% polyvinylpyrrolidone, and 1% SIB (Eq-short-mod). More (P <.02) oocytes with normal ultrastructural morphology were seen in fresh control and Eq-short groups than in Eq-long group. Metaphase-II (MIL) rates were higher (P <.05) for oocytes with expanded cumulus than compact cumulus in the control group, and higher (P <.05) for oocytes with expanded cumulus than compact cumulus in Eq-short and Eq-short-mod groups. No difference in MII rates was detected among groups within each type of COC. In conclusion, reduction of exposure time to VS better preserved oocyte ultrastructural features, and MII rates were higher for vitrified oocytes with expanded cumulus. This study advances our knowledge on potential alternatives for vitrification of immature equine oocytes. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Vitrification; Synthetic ice blocker; In vitro maturation; Equine oocyte